2001
DOI: 10.1007/s002130000639
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and leptin levels in patients with schizophrenia or related psychoses - a comparison between different antipsychotic agents

Abstract: The higher insulin level in the patients receiving olanzapine than in those receiving conventional antipsychotics, despite similar BMI, points to a probable influence of olanzapine on insulin secretion. The correlation between the insulin levels and the clozapine concentration indicates, in addition, an influence of clozapine on insulin secretion. The gender difference in leptin, i.e. females normally having higher leptin levels than males, was found in the conventional agent group, but not in the olanzapine o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2
5

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 43 publications
2
38
2
5
Order By: Relevance
“…The typical clinical path toward diabetes is associated with increased adiposity and subsequent changes in insulin sensitivity; however, the rapid onset of diabetes associated with SGA administration, and the disappearance of hyperglycemia after discontinuation in patients suggests that the development of diabetes in patients on SGAs may be an acute drug-related effect (Rettenbacher et al, 2007). There is evidence that OLZ has direct effects on glucose regulation, possibly leading to hyperinsulinemia, hyperglycemia, and insulin resistance (Baptista et al, 2002;Graham et al, 2005;Melkersson and Hulting, 2001;Seemuller et al, 2005). Of note, recent experiments show that SGAs may impair both the insulinresponsive glucose transport system, as well as lipolysis in adipocytes (Vestri et al, 2007), demonstrating that antipsychotic drugs may differentially affect insulin action and metabolism through direct cellular effects in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The typical clinical path toward diabetes is associated with increased adiposity and subsequent changes in insulin sensitivity; however, the rapid onset of diabetes associated with SGA administration, and the disappearance of hyperglycemia after discontinuation in patients suggests that the development of diabetes in patients on SGAs may be an acute drug-related effect (Rettenbacher et al, 2007). There is evidence that OLZ has direct effects on glucose regulation, possibly leading to hyperinsulinemia, hyperglycemia, and insulin resistance (Baptista et al, 2002;Graham et al, 2005;Melkersson and Hulting, 2001;Seemuller et al, 2005). Of note, recent experiments show that SGAs may impair both the insulinresponsive glucose transport system, as well as lipolysis in adipocytes (Vestri et al, 2007), demonstrating that antipsychotic drugs may differentially affect insulin action and metabolism through direct cellular effects in adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Most, but not all, cross-sectional studies found that women have higher serum leptin levels than men, even when men had greater BMI (Melkersson and Hulting, 2001;Arranz et al, 2004;Haupt et al, 2005). When studied prospectively, this gender discrepancy was gradually effaced as men demonstrated greater increases in serum leptin during several trials (Baptista et al, 2000;Hagg et al, 2001;Zhang et al, 2003).…”
Section: Gender Effectsmentioning
confidence: 99%
“…Cross-sectional studies with patients on various medications generally found that those exposed to olanzapine and clozapine were heavier, and had higher serum leptin levels (Hagg et al, 2001;Melkersson and Hulting, 2001;Melkersson and Dahl, 2003). Younger and thinner patients, regardless of medication, have lower serum leptin levels (Wang et al, 2006), and the association between the medication itself and leptin levels disappears when adjusted for differences in BMI (Smith et al, 2005).…”
Section: Features Of Weight and Leptin Changes During Antipsychotic Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Togo, encuentra un aumento en los niveles de esta proteína en pacientes en terapia prolongada con olanzapina y risperidona 39 , en tanto que el mismo grupo, en un estudio posterior, no encontró diferencias significativas en los niveles de adiponectina, pero sí elevación de leptina y disminución de ghrelina en pacientes expuestos a olanzapina por periodos menores a 4 semanas 40 . En relación a leptina, se ha planteado que se alteraría la relación fisiológica normal entre tejido adiposo y los niveles de circulantes 41,42 . La falta de consistencia en los resultados puede estar relacionada con la heterogeneidad clínica de esta enfermedad y las diferentes características de los pacientes seleccionados para estudio en cuanto a tiempo de evolución, uso de terapia antipsicótica y de otros fármacos asociados.…”
Section: Fármacounclassified